2017
DOI: 10.1103/physrevb.96.045414
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of the exciton built-in dipole moment in In(Ga)As quantum dots via nonlinear piezoelectric effect

Abstract: We show that anisotropic biaxial stress can be used to tune the built-in dipole moment of excitons confined in In(Ga)As quantum dots up to complete erasure of its magnitude and inversion of its sign. We demonstrate that this phenomenon is due to piezoelectricity. We present a model to calculate the applied stress, taking advantage of the so-called piezotronic effect, which produces significant changes in the current-voltage characteristics of the strained diode-membranes containing the quantum dots. Finally, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…In our previous work [24], we showed that the electrical polarization P and the corresponding built-in dipole moment in stress-tuned In x Ga 1−x As/GaAs QDs [27] are mainly influenced by one of the second-order terms in the expansion of P into strain (η), the dominant term is denoted by the coefficient B 124 . Based on that observation, an approximate formula to reproduce p as a function of applied shear in-plane stress σ appl xy was derived p/e ∝ A QD (σ…”
Section: Modeling Of Electric Dipolementioning
confidence: 99%
“…In our previous work [24], we showed that the electrical polarization P and the corresponding built-in dipole moment in stress-tuned In x Ga 1−x As/GaAs QDs [27] are mainly influenced by one of the second-order terms in the expansion of P into strain (η), the dominant term is denoted by the coefficient B 124 . Based on that observation, an approximate formula to reproduce p as a function of applied shear in-plane stress σ appl xy was derived p/e ∝ A QD (σ…”
Section: Modeling Of Electric Dipolementioning
confidence: 99%
“…where E 0 is the emission energy for F d = 0, and p z and β can be intuitively interpreted as the permanent electric dipole moment and polarizability of the corresponding complexes, respectively. 33,58,60,61 The quantity p z /e can be seen as the distance between the electron and hole probability densities along the z-axis. The results for QD1 and QD2 fitted by Eq.…”
Section: Permanent Electric Dipole Moments and Polarizability Of Neut...mentioning
confidence: 99%
“…By tuning the diode bias, not only the charge state is modified but also the magnitude of the electric field (F d ) along the QD growth direction. In turn, F d modifies the energy and spatial distribution of the confined single particle states as well as the Coulomb and exchange interactions among the charge carriers via the so-called quantum confined Stark effect (QCSE), leading to deep changes in the electronic and optical properties of the QDs [30][31][32][33] . Therefore, a fundamental understanding of the effects of F d in this kind of quasi-zero dimensional structures is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxially grown III-V semiconductor QDs offer such precise control where it has been shown that droplet epitaxy (DE) allows for a larger freedom in tuning the structural properties of quantum dot properties than is possible for quantum dots that are formed via the more common strain induced Stranski-Krastanov (SK) growth mode. By careful band gap engineering has it been possible to optimize QD nanostructures for various applications such as lasers [ 2 , 3 , 4 , 5 , 6 , 7 ], single and entangled photon emitters [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], photovoltaics [ 15 , 16 , 17 , 18 ], quantum dot infrared photodetectors [ 19 , 20 , 21 , 22 ] etc. Furthermore, the QDs are considered as promising building blocks for various quantum technologies such as quantum computing, quantum communication and quantum information technology [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%